The relationship among culturally responsive leadership and PLC practices in small schools in Peninsular Malaysia - Razali, Mohd Norlizam Mohd; Hamid, Aida Hanim A; Alias, Bity Salwana; Mansor, Azlin Norhaini (Journal of Education and Learning (EduLearn), 2024)
The study's goals were to find out how much culturally responsive leadership headmasters are employed and how many professional learning community (PLC) are set up in small schools. It also looked into the relationship between these two variables by using a questionnaire in a quantitative survey design, which was administered to 546 respondents out of 754 that had been distributed. Descriptive statistics were used to study the level of perception of all variables, and inferential statistics used Pearson’s correlation coefficient to study the relationship between the variables. The findings of the study showed that school headmasters practiced a culturally responsive leadership style, and teachers also participated a lot in PLC. Teacher participation in PLC had a significant relationship with culturally responsive leadership at the 0.05 significance level. The results of the study also showed that culturally responsive leadership accounts for 48.7% of the variance in teacher participation in PLC. This finding greatly suggests that culturally responsive leadership practices are important in contributing to teachers' practices in PLC, which in turn will improve student learning.